Bidirectional isolated DC-DC converter using dual full-bridge topology - Bautista, Marvin Ralph B.
This project aims to construct a DC-DC Converter capable of bidirectional power flow. The Low Voltage (LV) side is attached to a 24-Volt terminal while the High Voltage (HV) side is connected to 310 Volts. Power flow in both in directions is set to handle up to 500 Watts. The Dual Fullbridge Topology is intended to implement this converter. Each full-bridge works either as an inverter or a rectifier. The inversion process is controlled using a Pulse Width Modulation (PWM) circuit while the rectification is designed to be passive. When the LV side is supplying power, the PWM circuit is powered directly from the LV terminal. When power is supplied by the HV side, a fly back converter is used to power up the PWM circuit. The main isolation transformer has two windings, each winding connected to one full-bridge. The full-bridge performing inversion will convert the input DC voltage to an AC quasi-square signal which will be fed to one winding of the main transformer. The other winding then outputs a corresponding AC signal whose amplitude depends on the transformer's turns ratio. This signal passes through the other full bridge that performs rectification, yielding a DC voltage at the corresponding terminal.